ISSUES AND CAHALLENGES CONFRONTING STUDENT-MOTHERS ENROLLED FOR NCE PROGRAMME; CASE STUDY OF GOMBE STATE COLLEGE OF EDUCATION, BILLIRI - IDRIS ABUBAKAR; ABUBAKAR BALA; ABDULLAHI AHMED (International Studies Journal)
The intertwining nature of academic is quite challenging and this is escalated with motherhood responsibilities. The academic community mainly focuses on success, development, and never-ending competition without providing necessary support. This study will investigate the issues and challenges confronting student-mothers in College of Education Billiri. It also aimed at identifying available support system for their inclusion in higher education and also provide proper solution to such challenges so as to support and encourage student-mothers enrolled in such programmed for the betterment of women in the college. The study will adopt a qualitative approach and use purposeful sampling techniques to select 22 student-mothers age 21-40 years, Drown from college of education Billiri. Data will be collected through focus group discussion and semi-structure interview. Data generated will be analyze using qualitative content analysis. Which include Personal and educational need experiences of student-mothers at both school and home settings. The length of the survey should be question that will cover personal, marital, parental and educational information. Quantic survey data is to be analyst thematically in order to arrive at a description of student-mothers’ educational needs and experience. Relatively this research will investigate inclusive education measures for the student-mothers in the college. The current paper aims to address this issue. The research will be of paramount important to stakeholders like: Student-mothers, lecturers, parents, husband, and government at large in providing support services such as childcare and counselling for mothers to ensure their academic success.